Ferrites Synthesis and Applications - Khan, Maaz (IntechOpen, 2021)
Due to their unique electrical and magnetic characteristics, ferrites are useful for a wide range of technological applications including refrigerators, air conditioners, microwave ovens, radio and telecommunication devices, and computers. This book presents knowledge about ferrites, their fabrication, characterizations, and applications in different areas. It is a useful resource for students, scientists, and engineers working in the field of ferrites.